Tasgius (Tasgius) ater Gravenhorst 1802 - Majka, Christopher; Klimaszewski, Jan; Lauff, Randolph (Zenodo, 2008)
Tasgius (Tasgius) ater (Gravenhorst, 1802) NEW BRUNSWICK: Albert Co.: Mary's Point, 9.VIII.2002, C.G. Majka, barrier beach, under rock, (1, CGMC); Gloucester Co.: Saint Simon, 21.VIII.1983, P. Mal- let, (1, UMNB). NOVA SCOTIA: Antigonish Co.: Pomquet Beach, 2.IX.1996, R.F. Lauff, (1, STFX); Halifax Co.: West Dover, 7.IX.2003, C.G. Majka, seashore, coastal barrens, (1, CGMC); Sable Island, 5.VIII.1969, F.W. Scott, (3, NSMC); Sable Island, 9.IX.1977, 10.IX.1977, B. Wright, under boards, (2, NSMC); Lunenburg Co.: Petite Rivière, 3.IX.1954, D.C. Ferguson, (1, NSMC); Queens Co.: White Point Beach, 5.VIII.1953, J.H. McDunnough, (1, NSMC); Shelburne Co.: Bon Portage Island, 31.VII.1997, R.F. Lauff, (1, STFX); Yarmouth Co.: Port Maitland, 9.VIII.1988, J. Cook, beach, (1, JCC). PRINCE EDWARD ISLAND: Queens Co.: Cavendish, 14.VII.2002, C.G. Majka, coastal lagoon, under rock, (1, CGMC); North Rustico, 13.VII.2001, C.G. Majka, seashore, under rock, (1, CGMC). Majka and Klimaszewski (2008) newly recorded Tasgius ater in New Brunswick and on Prince Edward Island. Its distribution in the Maritime Provinces is shown in Majka and Klimaszewski (2008). It is also recorded from Newfoundland (Campbell and Davies 1991). As the above records indicate, this introduced species is often found beneath wood and stones at coastal sites, although it is also found in inland locations. It is a widely distributed Palearctic species known in North America since at least 1802 (Majka and Klimaszewski 2008). Published as part of Majka, Christopher, Klimaszewski, Jan & Lauff, Randolph, 2008, The coastal rove beetles (Coleoptera, Staphylinidae) of Atlantic Canada: a survey and new records, pp. 115-150 in ZooKeys 2 (2) on pages 134-135, DOI:10.3897/zookeys.2.2, http://zenodo.org/record/576408